The Effect of Downstream Flow Resistance for Kerosene and Water Separation on Efficiency T-Junction - Karminto; Suhartoyo (ARRUS Journal of Engineering and Technology, 2022)
This study aims to determine the separation of kerosene and water in a piping installation. It is very important to do research because it can reduce problems that arise in the distribution of drilling oil to further processing and distribution. T-Junction is a method used in this study, because the separator method is rarely used. The separation of kerosene and water types in the test using the T-Junction method, variations in downstream flow resistance of 42%, 57% and 72% resulted in a large kerosene separation efficiency of 100% at a mixed superficial velocity of 0.35 m/s, Jw= 0.25 m/s Jk = 0.10 m/s and at mixed superficial velocity 0.47 m/s, Jw = 0.22 m/s Jk=0.25 m/s, while 99% efficiency occurs at mixed superficial velocity 0 ,20 m/s , Jw= 0.10 m/s and Jk = 0.10 m/s. Water cut also greatly influences the phase separation. The lower the water cut, the higher the peak separation efficiency achieved